Review of Microwave Brazed Joint in Industry 4.0 - Tayier, Walisijiang.; Janasekaran, Shamini (International Journal of Psychosocial Rehabilitation, 2020)
The industry 4.0 is a significant planning of digitation of manufacturing which optimize the operations of production line quickly and efficiently. The industry 4.0 greatly influences on metal processing (joining) with digitation of new power sources that can increase metal joining efficiency and quality. The microwave brazed joining is one of the special features of joining technique (such as quick joining, saving time and low cost) in manufacturing joining system that is the most considerable technique of joining for industry 4.0 initials. The microwave brazed joining technique is a process in joining of similar and dissimilar metals (alloy-based and thermoplastic) which are jointed with filler metal or without filler metal (or powder) via microwave hybrid heating (radiation). Generally, the metal melted drops were flowed into joining (welding) area via microwave heating processing that is cools to become a strong joint in microwave applicator. In this paper, the microwave brazed joint technique is reviewed and extracted its basic function and parameters. It is a best method related to setting parameters and joining process that its results were compared with conventional brazing technique for industry 4.0 initials which can reduce processing cost and cycle time in specific metal joining process area. In addition, this paper also addressed the issue of conventional brazed processing that provided the gap of traditional brazed joint from previous research on brazing in industrial fields. In the part of the merit microwave joining, the advantages of microwave heating were illustrated through case study and research testing. Other than that, this paper also introduced industry 4.0 for microwave joining process that is focused on benefits and contributions with microwave (radiation).